The individual in the international legal system : continuity and change in international law - Parlett, Kate. (Cambridge, UK : Cambridge University Press, 2011)
'Kate Parlett's study of the individual in the international legal system examines the way in which individuals have come to have a certain status in international law, from the first treaties conferring rights and capacities on individuals through to the present day. The analysis cuts across fields including human rights law, international investment law, international claims processes, humanitarian law and international criminal law in order to draw conclusions about structural change in the international legal system. By engaging with much new literature on non-state actors in international law, she seeks to dispel myths about state-centrism and the direction in which the international legal system continues to evolve'--
'In the relatively open and flexible international system of the 21st century, the formal status of entities may seem to have little significance. Whether an individual is a direct right-bearer or an indirect beneficiary of an inter-state obligation may seem to be a distinction without a difference for the operation of the primary rules of international law: either way, the individual benefits from some substantive right, held either directly or through its state of nationality. But when it comes to the operation of secondary rules, the distinction assumes practical significance'--
Includes bibliographical references (p. 373-393) and index.
Keywords: Persons (International law).